Thyrotoxicosis Associated with Ustekinumab Treatment for Psoriasis. (18th August 2020) - Olabi, Bayanne; Ayob, Shanti
Abstract : Biologic treatments have revolutionised the management of psoriasis in recent years; however, data on their safety profile in large populations and long-term effects are being gathered on an ongoing basis. Ustekinumab is a monoclonal antibody that targets interleukin-12/23 used in the treatment of moderate-to-severe psoriasis. Here, we report the case of a 32-year-old Caucasian gentleman who developed thyrotoxicosis following the commencement of ustekinumab treatment. Following control of thyroid status by the Endocrinology team, this recurred after recommencement of ustekinumab on two further occasions over a 5-year period. This is the second known reported association of this nature. Awareness of these possible adverse effects is imperative in managing patients and informing decision-making, and further long-term studies will help elucidate the precise safety profiles of biologic treatments.